Organizational Loyalty in the Competitive Era - KERDPRATHUM, Phakrada; PUNPANICH, Noppadol; CHANTHAVONE, Thongphanh; KINGSADA, Youtthasack; VATTHANA, Mongkhoun (Souphanouvong University Journal Multidisciplinary Research and Development, 2021)
Organizational loyalty is a significant factor for organizations at the present that encounter the challenges of environmental changes. As a result, organizations in all industries have to confront competitive pressures inevitably. For this reason, organizations try to find ways to increase capabilities and to build sustainable competitive advantages in organizations through building organizational loyalty among members. In accordance with studying the concepts of organizational loyalty, it was found that the components of organizational loyalty proposed by scholars and executives consisted of: the first ones were to desire to maintain organizational membership and to work with realizing on to achieve organizational goals, followed by the confidence and acceptance of the organizational goals and values as well as having the pride to be a member and disclose a good image of the organizations including a sense of ownership.